Hand Recognition and Gesture Control Using a Wi-Fi Application in Smart Toye’s - Pallavi R. Chahare; M. N. Thakare; G. D. Korde (International Journal on Orange Technologies, 2021)
Hand gesture recognition is one of the systems that can detect the gesture of hand in a real time video. The gesture of hand is classified within a certain area of interest. In this, designing of the hand gesture recognition is one of the complicated jobs that involves two major problems. Firstly, is the detection of hand. Another problem is to create the sign that is suitable to be used for one hand in a time. This project concentrates on how a system could detect, recognize and interpret the hand gesture recognition through computer vision with the challenging factors which variability in pose, orientation, location and scale. To perform well for developing this project, different types of gestures such as numbers and sign languages need to be created in this system. The image taken from the real-time video is analyzed via Haar-cascaded Classifier to detect the gesture of hand before the image processing is done or in the other word to detect the appearance of hand in a frame. In this project, the detection of hand will be done using the theories of Region of Interest (ROI) via Python programming. The explanation of the results will be focused on the simulation part since the different for the hardware implementation is the source code to read the real-time input video. The developing of hand gesture recognition using Python and OpenCV can be implemented by applying the theories of hand segmentation and the hand detection system which use the Haar-cascade classifier.